An Approach to Assess Learning Conditions, Effects and Outcomes in Environmental Governance. (19th October 2017) - Armitage, Derek; Dzyundzyak, Angela; Baird, Julia; Bodin, Örjan; Plummer, Ryan; Schultz, Lisen
Abstract: We empirically examine relationships among the conditions that enable learning, learning effects and sustainability outcomes based on experiences in four biosphere reserves in Canada and Sweden. In doing so, we provide a novel approach to measure learning and address an important methodological and empirical challenge in assessments of learning processes in decision‐making contexts. Findings from this study highlight the effectiveness of different measures of learning, and how to differentiate the factors that foster learning with the outcomes of learning. Our approach provides a useful reference point for future empirical studies of learning in different environment, resource and sustainability settings. © 2017 The Authors. Environmental Policy and Governance published by ERP Environment and John Wiley & Sons Ltd